The association of self-compassion with depressive temperament and reading habit - Masaki Eto; Takeshi Terao; Moriaki Satoh; Nobuko Kawano; Akari Sakai; Mari Akase; Hirofumi Hirakawa; Kentaro Kohno (Academia Mental Health & Well-Being)
Self-compassion has three important components: self-kindness, common humanity, and mindfulness, which may help people through hardships. Few studies have reported how temperament or lifestyle habits affect self-compassion in individuals. Therefore, we explored the effects of temperament and lifestyle habits on self-compassion using a dataset of 130 apparently healthy participants. Multiple regression analyses with the stepwise method were conducted for the total Self-Compassion Scale (SCS) scores as the dependent variable, with age, sex, education, scores of five temperaments (depressive, cyclothymic, irritable, anxious, and hyperthymic), and weekly hours for four lifestyle habits (physical exercise, music listening, reading, and meditation) as independent variables. Self-compassion, measured by SCS scores, was significantly and positively associated with reading habit, and significantly and negatively associated with depressive temperament. The present findings suggest a possibility that self-compassion may be negatively associated with depressive temperament, but positively associated with reading habit. Therefore, reading habit may be one of the useful strategies for protecting mental health via self-compassion, particularly in people with depressive temperament. Nonetheless, this is a cross-sectional study and further studies are required to investigate the causal relationship.